Energy metabolism in the fundamental throwing techniques of judo - Ogawa, S.; Imada, Y.; Akutsu, K.; Yoshino, S.; Sugimoto, R.; Seki, T. (Association for the Scientific Studies on Judo, Kodokan, 1958)
Since A. V. Hill`s studies on energy metabolism much work has been done in this field. For example, studies made by Liljestrand, Sato, and Yoshioka in swimming; Liljestrand in skating; Liljestrand and, Henderson in boating; A. V. Hill, Furusawa and Sargeant, Klatsclikow, and Ogasawara in running; Yoshida, Ogasawara, and Ishii in calisthenics; Sugimoto in mountaineering; Iino in skiing, etc. are well known. Recently, Yamaoka et al. have made extensive studies on the amount of energy required in soccer, baseball and rugby. Lately as judo has become internationally popular, interest in the scientific studies on judo from various angles has been aroused. To begin with a study on the energy metabolism during the performance of judo was selected. However, depending on the physique and skill of the individuals under investigation a wide fluctuation in the results is to be expected. In order to avoid this, performers with approximately the same physique and skill, and also with a considerable training experience were selected as experimental subjects. They were also made to perform the various representative techniques with a constant speed, while their energy consumption was being measured.